The last ghetto: an everyday history of Theresienstadt - Hájková, Anna (Oxford scholarship online, 2020)
'The Last Ghetto' is a social and cultural history of Terezâin, or Theresienstadt, a transit ghetto for Central and Western European Jews prior to their deportation for murder in the East. It offers the first analytical case study of a Holocaust victim society that explains human behavior in extremis, and demonstrates how prisoners created new social hierarchies, reshaped their conceptions of family, and developed new loyalties. Based on extensive research in archives around the world and empathetic reading of victim testimonies, this history of everyday life in a prisoner society reveals the many forms of agency and adaptation in Nazi concentration camps and ghettos.